Analisis Laporan Keuangan Bank BRI: Dampak Penerapan Standar Akuntansi Keuangan terhadap Kinerja Keuangan - Yuliana Oktavianus (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
This study aims to analyze the impact of Financial Accounting Standards (FAS), particularly PSAK No. 71, on the financial performance of Bank Rakyat Indonesia (BRI). The implementation of PSAK No. 71 replaces the Incurred Loss model with the Expected Credit Loss Model (ECL) which is more proactive in anticipating credit risk. The analysis was carried out using a descriptive quantitative method based on Bank BRI's financial statements for 2021-2023. The results showed that the implementation of PSAK No. 71 contributed to increasing the transparency and accuracy of financial statements, which is reflected in fluctuations in Return on Assets (ROA) and Return on Equity (ROE). In addition, Non-Performing Loan (NPL) has decreased, indicating improvements in credit risk management. However, challenges in the implementation of this standard are still found, especially related to the estimation of potential credit losses that are affected by macroeconomic conditions. This research provides insights for banks and regulators in improving transparency and financial stability in the Indonesian banking industry.